2019
DOI: 10.1136/neurintsurg-2019-015225
|View full text |Cite
|
Sign up to set email alerts
|

Peri-procedural stroke or death in stenting of symptomatic severe intracranial stenosis

Abstract: Background and purposeThere are limited data on predictors of 30-day stroke or death in patients with symptomatic intracranial atherosclerosis (sICAS) undergoing stenting. We aim to determine the factors associated with stroke or death at 30 days in the stenting arm of the SAMMPRIS trial.MethodsThis is a post-hoc analysis of the SAMMPRIS trial including patients who underwent angioplasty/stenting. We compared patient-specific variables, lesion-specific variables, procedure-specific variables, and FDA-approved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The open-cell design of the Neuroform EZ stent was thought to be associated with this result [18]. However, the exact risk factors for these perioperative complications after PTAS with the Enterprise stent are still uncertain, and further research is needed [37]. In particular, for high-grade stenosis, the low complication rate in our study supported the safety of Enterprise stent implantation in ICAS treatment.…”
Section: Discussionsupporting
confidence: 59%
“…The open-cell design of the Neuroform EZ stent was thought to be associated with this result [18]. However, the exact risk factors for these perioperative complications after PTAS with the Enterprise stent are still uncertain, and further research is needed [37]. In particular, for high-grade stenosis, the low complication rate in our study supported the safety of Enterprise stent implantation in ICAS treatment.…”
Section: Discussionsupporting
confidence: 59%
“…In a post hoc analysis from the SAMMPRIS trial, lesion length was an independent predictor of 30-day stroke or mortality in patients undergoing angioplasty and stenting. 77 Likewise, pretreatment stenotic degree has been established as a strong predictor for in stent restenosis. 78,79 Therefore, the combination of severe stenosis and long plaque length represents a significant challenge.…”
Section: Icad Lesion Classification: Technical and Prognostic Implica...mentioning
confidence: 99%
“…We performed a filter on the variables described above based on the univariate analysis results (variables with P ≤ 0.200) and on clinical experience and previous results observed in similar published reports ( 16 , 17 ) for the multivariate analysis. The significant factors are showed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, greater stenosis, low mRS scores, and clopidogrel loading increased the risk for hemorrhagic stroke ( 16 ). When stroke and death were defined as a combined endpoint for analysis, only nonsmoking and longer lesions were associated with increased risk, but did not exhibit good predictive values ( 17 ). Our findings revealed that lesions located at arterial origins or bifurcations exhibited a higher short-term postoperative risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation